2020
DOI: 10.1002/er.5255
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of sensible and latent heat thermal energy storage systems

Abstract: Summary The thermal energy storage is an essential subsystem for solar thermal energy systems. Few experimental studies are available to compare the performance of sensible and latent thermal energy storage systems for the same storage configurations. The comparison can provide guidance in selecting the storage system for particular solar thermal applications. The present work focuses on the experimental investigation of sensible and latent thermal storage systems with different mass flow rates. Concrete spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Xia et al 12 developed a new mathematical model to analyze PCM's melting and solidification process in cylindrical containers using an effective heat capacity method. Suresh and Saini 13 performed various experimental studies to explore the performance of the TES system, which consists of a tank filled with paraffin spherical capsule and concrete capsule placed at the bottom of storage tank acts like sensible heat media. They found that the charging time of the latent heat system is superior to the sensible system by about 10.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al 12 developed a new mathematical model to analyze PCM's melting and solidification process in cylindrical containers using an effective heat capacity method. Suresh and Saini 13 performed various experimental studies to explore the performance of the TES system, which consists of a tank filled with paraffin spherical capsule and concrete capsule placed at the bottom of storage tank acts like sensible heat media. They found that the charging time of the latent heat system is superior to the sensible system by about 10.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Ming et al 16 studied the dual-media thermocline thermal storage tank and found that the discharging performance was influenced to some extent by varying size and the fluid inlet velocity for all cases and also influenced the corresponding effective discharging efficiency and discharging time. Suresh and Saini [17][18][19] reported that the combined use of PCM capsules and concrete spheres increases the discharge time by improving energy utilization. Based on the results, it was recommended that the combined sensible and latent heat storage systems are a promising energy storage method since it reduces the cost and increase the energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Energy can be stored either in the form of sensible or latent heat; the later possesses a higher energy storage density, capable of storing or retrieving energy in a nearby isothermal condition. 3,4 . The phase change materials (PCM) are ubiquitously utilized in latent heat thermal energy storage systems and numerous PCMs are available under the categories of organic, inorganic and eutectic mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal energy storage (TES) system is the most promising one, as the stored energy can be directly consumed in the form of hot or cold energy, minimizing the energy losses during conversion in different applications 1,2 . Energy can be stored either in the form of sensible or latent heat; the later possesses a higher energy storage density, capable of storing or retrieving energy in a nearby isothermal condition 3,4 …”
Section: Introductionmentioning
confidence: 99%